A Biomechanical Comparison of Knee Stability after Posterolateral Corner Reconstruction: Arciero vs. LaPrade. Issue 7 (21st July 2017) - Treme, Gehron; Ortiz, Gabriel; Gill, George K.; Menzer, Heather Marie; Johnson, Paul J.; Salas, Christina; Qeadan, Fares; Schenck, Robert C.; Richter, Dustin L.; Wascher, Daniel C.
Objectives: The Posterolateral Corner (PLC) is an area of the knee that does not receive adequate research recognition despite its functionality and contribution to the overall stability of the knee. Until recently, its anatomy and biomechanics have been poorly understood which has led to the creation of multiple reconstruction methods. Two frequently used techniques are the Arciero and LaPrade reconstructions. Both have shown promising outcomes, but the two techniques have never been compared against each other from a biomechanical perspective. The objective of this study was to identify which reconstruction technique (Arciero vs. LaPrade) best restores stability to an isolated posterolateral corner (PLC) injury and injuries of the PLC which occur concurrently with injury to the tibiofibular ligament (tib-fib) and the anterior cruciate ligament (ACL), respectively. Methods: Ten matched paired fresh-frozen cadaveric specimens from mid femur to foot were used. The Semitendinosus, Gracilis, and Achilles tendons were harvested from each specimen to use as allografts for the corresponding reconstructions. Mechanical Testing: To examine the significance of PLC instability a custom made testing fixture was created to isolate and test for 10 Nm Varus Angulation (VA) and 5 Nm External Rotation (ER) at 0, 20, 30, 60, and 90 degrees of flexion about the knee joint. Data Acquisition: 8 Optitrack Motion Capture cameras were used to acquire VA and ER data through the use of 3 rigid body marker sets. The motion capture software recorded the initial and final positions of the marker sets under loading. Measures were taken of the intact knee, at post-sectioning of the PLC, and post-reconstruction (Arciero or LaPrade). Subsequently, half the specimens were subject to sectioning of the tib-fib ligament and half to sectioning of the ACL. Measures were collected of each. Data Analysis: Multivariate Analysis of Variance (MANOVA) was used to assess the mean differences over the five angles at each stage. The Wilks' Lambda statistic and significance level of 5% were used to establish statistically significant differences. Results: Data from paired, intact knees were found to be statistically similar confirming that all subsequent tests would not be affected by specimen variabilities. Post-PLC sectioning data for both groups showed significant instability from intact data, but were not different from each other. Data analysis concluded that there was no statistically significant difference between the LaPrade and Arciero techniques post-reconstruction. Both techniques were able to regain >80% of the stability of the intact knee. Post-tib-fib sectioning, ER instability was increased for all Arciero reconstructions at 90º flexion (p=0.01). Additionally, VA instability was increased for Arciero reconstructions at all flexion angles, but not significantly. A positive post-hoc parallel profile test indicates that the post-tib-fib VA data may have been significant with a larger sample size. Sectioning the ACL showed no difference between the two techniques. Conclusion: The outcome measures of this study show no statistical differences between the Arciero and LaPrade techniques for VA and ER at varying degrees of knee flexion. Post-hoc tests showed that the LaPrade technique may be the preferred option when PLC injury is concurrent with injury to the tib-fib ligament.